2000
DOI: 10.1097/00005373-200002000-00002
|View full text |Cite
|
Sign up to set email alerts
|

Is Routine Arteriography Mandatory for Penetrating Injuries to Zone 1 of the Neck?

Abstract: Patients with penetrating wounds to zone I who have no evidence of vascular injury on PE and who have normal findings on CXR may not require routine arteriography. Further study is needed to confirm these findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
41
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(41 citation statements)
references
References 10 publications
0
41
0
Order By: Relevance
“…Demetriades et al [10] conducted a prospective trial evaluating the use of physical examination in PNI patients; they demonstrated that the lack of hard signs of vascular and aerodigestive tract injuries could reliably exclude the need for operative repair with the negative predictive value of 100%. Retrospective studies also showed that physical examination, combined with a negative chest X-ray; could be used to rule out significant vascular injuries (negative predictive value 100%) in zone I PNI patients [14,15]. Hence, observation alone in asymptomatic PNI patients, regardless of the zone, seems to be a safe approach.…”
Section: Discussionmentioning
confidence: 99%
“…Demetriades et al [10] conducted a prospective trial evaluating the use of physical examination in PNI patients; they demonstrated that the lack of hard signs of vascular and aerodigestive tract injuries could reliably exclude the need for operative repair with the negative predictive value of 100%. Retrospective studies also showed that physical examination, combined with a negative chest X-ray; could be used to rule out significant vascular injuries (negative predictive value 100%) in zone I PNI patients [14,15]. Hence, observation alone in asymptomatic PNI patients, regardless of the zone, seems to be a safe approach.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11][12] At this time, despite the vast amount of research completed in this area, no unified consensus on the optimal management strategy for penetrating neck injuries exists.…”
Section: Discussionmentioning
confidence: 99%
“…For the remaining patients, management options include mandatory exploration, mandatory imaging, and selective physical examination directed imaging and intervention. [1][2][3][4][5][6][7][8][9][10][11][12] Mandatory exploration of the neck is associated with a high rate of negative exploration with its attendant risks, time, cost and potential for complication. Mandatory screening of all patients with imaging also has its drawbacks.…”
mentioning
confidence: 99%
“…Penetrating injuries to zones 1 and 3 parlay notorious difficulty in obtaining emergent surgical access and therefore require an urgent CT screening examination to rule out injury in the presence of any abnormality detected on physical examination or chest radiograph. 2 Vascular injury in particular can be studied with CT angiography, 3 percutaneous angiography or duplex ultrasonography, 4 depending on the resource profile of a given centre. Metal fragments (missile, shrapnel) may create artifact limitations that are more easily bypassed using formal percutaneous angiography.…”
Section: Neck Injuriesmentioning
confidence: 99%